Model Transaformasi Ekonomi Rendah Karbon berbasis Wakaf Hijau dan Wakaf Uang - Shofura Auliya; Qisty Hanifah Mardiyah; Arisetyo Raiz Al Mumtaz; Hilmi Zaki Ibrahim (Gunung Djati Conference Series, 2026)
This article aims to formulate an alternative waqf-based financing model to support the transition to a low-carbon economy in Indonesia. This model integrates green waqf and cash waqf as strategic instruments in addressing the challenge of limited conventional funding for environmentally friendly projects. This research employs a qualitative approach using the literature review method, through the analysis of relevant literature related to waqf, sustainable finance, and green economic transition. The results of the study indicate that the synergy between green waqf as a form of physical asset investment is capable of forming a participatory, inclusive, and sharia-compliant financing ecosystem, and cash waqf as a source of flexible financing. The proposed model, namely the Green Asset Initiation Model, encourages the acceleration of the development of green assets such as conservation land, renewable energy, and organic farming. Consequently, this model has the potential to strengthen the role of Islamic social finance in supporting sustainable development, increasing community involvement in environmental preservation, and supporting the achievement of carbon emission reduction targets systemically and sustainably.